RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L) TERHADAP PEMBERIAN PUPUK ORGANIK PADAT DAN PUPUK ORGANIK CAIR - Irna Syofia; Hadriman Khair; Khairul Anwar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The aims of this study was to evaluate the response of growth and yield of green bean (Vigna radiata L.) against solid organic fertilizer and liquid organic fertilizer. The design used was a factorial randomized block design (RAK-F) with the two factors studied, namely: Factor Nafos Guano organic fertilizer dense (N) consists of 4 levels of treatment that is N0 = without giving, N1 = 16,88 g / plot (75 kg / ha), N2 = 33,75 g / plot (150 kg / ha) and N3 = 50,63 g / plot (225 kg / ha). Factors Supermes liquid organic fertilizer (S) comprises 3 levels of treatment that is S0 = without giving, S1 = 1,5 cc / liter of water and S2 = 3 cc / liter of water. The parameters measured were plant height, number of branches, days to flowering, pod weight per plant, weight of pods per plot, seed weight per plot and weight of 100 seeds. The results showed that administration of solid organic fertilizer significantly affect the parameters of plant height, weight of pods per plant and 100 seed weight. Dose of the best applications that N3 = 50,63 g / plot (225 kg / ha). Liquid organic fertilizer significantly affect the parameters of plant height, days to flowering and pod weight per plant. Dose of the best applications that S2 = 3 cc / liter of water. The interaction between organic fertilizer liquid organic fertilizer dense and not a real effect on all parameters measured. Green bean crop production due to solid organic fertilizer and liquid organic fertilizer is as much as 9427.63 g (1.16 tonnes / ha). Keywords: green beans, nafos guano and supermes